Nitrogen regulation of the xyl genes of Pseudomonas putida mt‐2 propagates into a significant effect of nitrate on m‐xylene mineralization in soil. Issue 6 (26th August 2016) - Svenningsen, Nanna B.; Nicolaisen, Mette H.; Hansen, Hans Christian B.; de Lorenzo, Victor; Nybroe, Ole
Summary: The nitrogen species available in the growth medium are key factors determining expression of xyl genes for biodegradation of aromatic compounds by Pseudomonas putida . Nitrogen compounds are frequently amended to promote degradation at polluted sites, but it remains unknown how regulation observed in the test tube is propagated into actual catabolism of, e.g. m ‐xylene in soil, the natural habitat of this bacterium. To address this issue, we have developed a test‐tube‐to‐soil model system that exposes the end‐effects of remediation practices influencing gene expression of P. putida mt‐2. We found that NO3 − compared with NH4 + had a stimulating effect on xyl gene expression in pure culture as well as in soil, and that this stimulation was translated into increased m ‐xylene mineralization in soil. Furthermore, expression analysis of the nitrogen‐regulated genes amtB and gdhA allowed us to monitor nitrogen sensing status in both experimental systems. Hence, for nitrogen sources, regulatory patterns that emerge in soil reflect those observed in liquid cultures. The current study shows how distinct regulatory traits can lead to discrete environmental consequences; and it underpins that attempts to improve bioremediation by nitrogen amendment should integrate knowledge on their effects on growth and on catabolic gene regulation under natural conditions. Abstract : Nitrogen regimes can determine expression of xyl genes for biodegradation of aromatic compounds by Pseudomonas putida mt‐2 in pure culture. However, to date it is not known if knowledge obtained from laboratory cultures is applicable to more natural systems as soils. We have developed a test‐tube‐to‐soil model system for studying the impact of 'environmental conditions' on xyl gene expression of P. putida mt‐2, and found that NO3 − compared with NH4 + had a stimulating effect on xyl gene expression in pure culture as well as in soil, and that this stimulation was translated into increased m ‐xylene mineralization in soil.